Divide in Ferguson: Social Media, Social Context, and Division. (July 2018) - Park, Yong Jin; Jang, S. Mo; Lee, Hoon; Yang, Grace S.
We examine the patterns of social polarization, with the case of Michael Brown shooting as an empirical basis for discussing the role of social media in promoting polarized viewpoints. In doing so, we test a model that synthesizes the interplay between text polarity in Twitter and four attributes of U.S. cities ( N = 216): (1) geographic location, (2) race, (3) poverty, and (4) technological condition. Our findings supported hypothesized functions of socio-environmental traits. However, the extents of polarization in tweet-texts were subtler than expected. Furthermore, the finding concerning poverty suggests that certain urban environments are more conducive to exacerbating racial tensions, reproducing them into social media narratives. We suggest future studies and discuss the implications for societal divide.